Long‐term trends in sex difference in bladder cancer survival 1975‐2009: A population‐based study in Osaka, Japan - Jo Aoe; Yuri Ito; Keisuke Fukui; Masashi Nakayama; Toshitaka Morishima; Isao Miyashiro; Tomotaka Sobue; Tomio Nakayama (Cancer Medicine)
Abstract In Japan, a study using population‐based cancer registry data from six prefectures revealed a difference in bladder cancer survival between men and women. However, the period of the study was limited to 1993‐2006. The recent introduction of immune checkpoint inhibitors, which have proved to be effective for the treatment for bladder cancer, has led to a rising demand for analysis of long‐term trends in net survival in order to accurately assess the effect of the new treatment. The aim of the present study was to examine long‐term trends in sex difference in bladder cancer net survival using large‐scale population‐based cancer registry data from Osaka, Japan (17,500 cases from 1975 to 2009). We also evaluated sex difference in bladder cancer survival after adjustment for stage, histologic type, and other prognostic factors. We showed the long‐term trend of five‐year net survival for each stage and found that women had poorer five‐year net survival than men for the whole study period. The risk of death from bladder cancer was higher among men than women even after adjusting for period at diagnosis, histologic type, stage, age group, and treatment (Excess hazard ratios: 1.17; 95% Confidence interval: 1.10‐1.25).